Epigenetic age estimates and childhood environment: an interdisciplinary analysis of a Bangladesh-UK cohort - Evaristo Cursino da Silva, Maria Luisa (2023)
Background: Ageing is not a negative phenomenon but ageing prematurely can lead to adverse health outcomes. This study investigates the rate of epigenetic ageing across migrant and non-migrant populations of girls living in the UK. First-generation Bangladeshi migrant girls are the focus of this study as we pursue a better understanding of whether migration as a socio-economic factor can affect epigenetic ageing. The thesis builds on the work by Houghton and colleagues, who previously investigated the relationship between socio-economic factors and pubertal timing across a larger cohort than the one studied in this thesis. Methods: For this thesis, the DNA methylation data from the saliva samples of a subset of data donated from Houghton et al.’s study (115 girls) was analysed to predict epigenetic age estimates based on the methylation levels of buccal epithelial cells. DNA methylation-based epigenetic clocks were used as a proxy to predict the biological ages of the cohort, which was composed of Bangladeshi girls born and raised in Sylhet Town, Bangladesh (n=43), first-generation Bangladeshi girls who left Bangladesh to live in the UK (n=24), second-generation Bangladeshi girls born in the UK to immigrant parents (n=27), and white British girls born in the UK (n=21). Results: Across the six clocks used in this study, epigenetic age estimates from the PedBE clock yielded the most closely correlated results to the populations’ chronological ages. The skin and blood clock also delivered similarly correlated results. According to data harvested from most clocks used in this study, first-generation migrant Bangladeshi girls had a higher epigenetic age acceleration rate. However, ANOVA tests concluded that the discrepancy was not statistically significant with the sample size available. Conclusion: The PedBE clock’s accuracy is linked to the tissue-type and age range from this study’s cohort, which met the specificity parameters used to design the PedBE clock. This study identified migration as a socio-economic stressor that may contribute to accelerated biological ageing. Although the divergence across groups was not statistically significant, it alludes to a trend corroborated in later life among migrant Bangladeshi women in the UK. The work undertaken here implores further investigation and action from policymakers to better support immigrant communities to the UK, particularly those coming from the Global South.